P2X4 Receptor Function in the Nervous System and Current Breakthroughs in Pharmacology - Stokes, Leanne; Layhadi, Janice A.; Bibic, Lucka; Dhuna, Kshitija; Fountain, Samuel J. (Frontiers in Pharmacology, 2017)
ATP is a well-known extracellular signalling molecule and neurotransmitter known to activate purinergic P2X receptors. Information has been elucidated about the structure and gating of P2X channels following the determination of the crystal structure of P2X4 (zebrafish), however there is still much to discover regarding the role of this receptor in the central nervous system (CNS). In this review we provide an overview of what is known about P2X4 expression in the CNS and discuss evidence for pathophysiological roles in neuroinflammation and neuropathic pain. Recent advances in the development of pharmacological tools including selective antagonists (5-BDBD, PSB-12062, BX430) and positive modulators (ivermectin, avermectins, divalent cations) of P2X4 will be discussed.